Assessment of physicochemical properties of Besease wetland soils, Ghana - Atta-Darkwa, Thomas; Asomaning, Samuel Kwasi; Agbeshie, Alex Amerh (African Journal of Agricultural Research, 2020)
The shallow and erodible soils of low fertility uplands have led to farmers extending their cultivable areas to wetlands for optimal crop production since these systems have the potential for exploitation in the dry season. To ensure its sustainable use, the physicochemical and the hydrological characteristics of the valley bottom should be ascertained. Studies were conducted to assess the suitability of wetlands for crop production by analysing the physicochemical properties of Besease wetland soils. Soil samples were collected from specific sites and profile pits for physical and chemical analysis in the laboratory. Field experiments were also conducted for soil physical properties. Soil textural analysis revealed that the average texture of the Besease inland valley was sandy loam with the distribution of sand, silt and clay as 55.42, 35.04 and 9.50%, respectively. Bulk density and moisture content on the field increased with depth in all profiles. Results of hydraulic conductivity using the mini disk infiltrometer ranged from 2 to 88.3 cm/day. The infiltration rate on the studied wetland ranged from 0.02 to 0.78 cm/min. The pH, OC, TN and CEC of the soil profile distribution for site P11-P14 obtained ranged from 6.9-4.6, 4.69-0.19%, 0.2-0.01%, 9- 2.6 meq/100 g down the horizon respectively. The study unraveled a sustained plant nutrient availability and elongation of water level ponding which will result in increased water storage under rice cultivation in the studied wetland.
Keywords: Wetlands; physicochemical; crop production; nutrient; water storage; Ghana; University of Energy & Natural Resources; ACE: Energy and Environmental Sustainability